‘VALENTONES’, ‘ALCALDES DE BARRIO’ AND PARADIGMS OF CIVILITY.CONFLICTS AND ACCOMODATIONS IN SANTIAGO OF CHILE, XVIII CENTURY. - Undurraga Schüler, Verónica (Revista de Historia Social y de las Mentalidades, 2011)
This work studies the polisemous universe of the practices and the speeches of violence, civility and social control that circulated in the city of Santiago throughout XVIII century. When analyzing plots of meaning of the narrations of interpersonal violence, related to the construction of a hegemonic masculinity and protected in speeches of honour, the study explores the survival of old practices of private revenge. Also, it examines the tensions and negotiations established between these and the strategies of social control undertaken by the Bourbons’ state and exerted through a microphysics of daily control, incarnated as much in the functions of the ‘Alcaldes de barrio’ like in the socialization of a civility paradigm. The latest allows putting under evaluation the fissures and the strengths of the foundations of the Bourbon’s administration.
Keywords: Violence; civility; social control; justice; Bourbon’s administration